FAKTOR – FAKTOR YANG MEMPENGARUHI KINERJA PERBANKAN SUATU STUDI PADA BANK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Liviawati Liviawati; Rita Wiyati (PEKBIS, 2017)
A bank that has good management if the bank can show a good performance in thisregard is reflected by how big the bank's ability to generate profits or profitability. PTBank TBK jewel reported poor performance in the first half of 2016 with a net loss ofRp 835.67 billion or Rp 65 per share when compared to the performance in the firsthalf of 2015 and the net profit was 837.31 billion or Rp 70 per share, Bank Mandiri,one of the largest state banks in Indonesia through the same thing. Independentbank profits decreased by 25.7%, PT Bank Mega TBK recorded a relatively flatperformance in the first half of 2016. Net income issuers coded mega bankdecreased by 2.71% to 539 billion. PT national pension T BK savings bank (theBank) reported net income declined 6.9% to 1.75 trillion at the end of last yearcompared to the previous year of 1.88 trillion. PT Bank Artha Graha InternationalTbk is still weak in the first three months of 2016. This can be seen from the bank'snet profit INPC issuers coded these fell 33.33% to 32.28 billion, The aim of thisstudy was to examine the effect of capital to bank runs, to test the effect of liquidityon the banks' performance, to test the effect on the performance of bank profitabilityand to test the effect of buying power on the performance of the bank. The analyticaltool used in processing the data in this study using multiple regression statisticalanalysis. Based on the results of the statistical test of the obtained results, to bepartial test result that capital or liquidity or profitability or risk or purchasing powerdoes not affect the profitability (in this case measured by ROA). But based on thesimultaneous test of the obtained results that capital, liquidity, profitability, risk andGDP effect on profitability (ROA).